How prior experience, cognitive skills and practice are related with eye-hand span and performance in video gaming - Markus Nivala; Agnes Cichy; Hans Gruber (Journal of Eye Movement Research)
Research has shown that performance in visual domains depends on domain-specific cognitive and perceptual adaptations that result from extensive practice. However, less is known about processes and factors that underpin the acquisition of such adaptations. The present study investigated how prior experience, cognitive skills, task difficulty and practice effect eye-hand span (EHS) and performance in video gaming. Thirty-three participants played a platformer video game in a pre-test/practice/post-test experiment. Eye movements and keypresses were recorded. The results show that a short practice period improved performance but did not increase EHS. Instead, EHS was related to task difficulty. Furthermore, while EHS correlated with initial performance, this effect seemed to diminish after practice. Cognitive skills (concentration endurance, working memory, mental flexibility and executive functioning) predicted performance in some parts of the experiment. The study offers insights into the early development of visual adaptations and performance.